2009
DOI: 10.1523/jneurosci.4707-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Fornix Microstructure Correlates with Recollection But Not Familiarity Memory

Abstract: The fornix is the main tract between the medial temporal lobe (MTL) and medial diencephalon, both of which are critical for episodic memory. The precise involvement of the fornix in memory, however, has been difficult to ascertain since damage to this tract in human amnesics is invariably accompanied by atrophy to surrounding structures. We used diffusion-weighted imaging to investigate whether individual differences in fornix white matter microstructure in neurologically healthy participants were related to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
88
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 36 publications
11
88
2
Order By: Relevance
“…These results are consistent with the view that the fornix, together with the hippocampus, is critically and specifically involved in particular aspects of episodic memory (Aggleton et al, 2000;Rudebeck et al, 2009). This model posits distinct, but interleaved, networks for recollection and familiarity-based recognition (Aggleton and Brown, 2006), in which the fornix is vital for recollection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with the view that the fornix, together with the hippocampus, is critically and specifically involved in particular aspects of episodic memory (Aggleton et al, 2000;Rudebeck et al, 2009). This model posits distinct, but interleaved, networks for recollection and familiarity-based recognition (Aggleton and Brown, 2006), in which the fornix is vital for recollection.…”
Section: Discussionsupporting
confidence: 91%
“…Recent DWI studies have found that variations in fornix microstructure in young people correlate selectively with recollec-tive memory (Rudebeck et al, 2009), closely supporting clinical studies of fornix pathology (Aggleton et al, 2000;Tsivilis et al, 2008). As only the fornix was examined, the specificity of this association remains unclear.…”
Section: Introductionmentioning
confidence: 74%
“…As focal damage to the fornix and mammillary bodies results in impaired performance that resembles that of hippocampal damage (Dusoir et al 1990;Tsivilis et al 2008;Rudebeck et al 2009;Vann et al 2009b), it has been suggested the study of hippocampusbased memory should be extended to include the fornix and mammillary bodies as part of the "extended hippocampal system" (Aggleton and Brown 1999).…”
Section: Hippocampus and Mtlmentioning
confidence: 99%
“…In addition, there was evidence of microstructural alteration in the residual fornix and in the other temporal association tracts, the uncinate, and PHC. The role of the fornix as the predominant correlate of recall performance-found in young 29 and healthy older 5 adults-was not reproduced in patients with MCI. In patients, the strongest correlate of verbal free recall was left PHC structure.…”
mentioning
confidence: 91%
“…36 The contrast in pattern of correlations between controls and MCI raises the possibility that this is also true of the breakdown of human memory in disease. Table 2 Tract-specific average (SD) indices of white matter microstructure in the fornix, uncinate fasciculus, parahippocampal cingulum, and corticospinal tract for healthy controls (n 5 20) and patients with MCI (n 5 25) The specific association between fornix microstructure and recollection-based episodic memory was predicted by earlier MRI analyses 5,29 and by the impact of lesions that selectively disrupt fornical fibers. 25 One interpretation of the present results is a disproportionate recruitment of nonfornical pathways to support recognition memory.…”
mentioning
confidence: 98%